2012
DOI: 10.4172/2161-0703.1000e109
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Microbiology: Reemphasizing the Role of Anaerobic Bacteria in Human Infections

Abstract: J o u rn al of M e d ic a l Mi crob io lo g y & Diagno s is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…5 Foregoing studies have demonstrated that in retaliation to pernicious root canal microflora particularly bacteria, the diabetic host may mature with more consequential infections. 4 When the diabetic and non-diabetic population is compared, patients with diabetes mellitus and periapical lesion have shown notably diminished healing succeeding endodontic therapy. 6 Hence, this study aims to isolate obligate anaerobes and facultative anaerobes from root canal of non-vital teeth in diabetic (Type II) and non-diabetic patients.…”
Section: Ijcrr Section: Healthcarementioning
confidence: 99%
“…5 Foregoing studies have demonstrated that in retaliation to pernicious root canal microflora particularly bacteria, the diabetic host may mature with more consequential infections. 4 When the diabetic and non-diabetic population is compared, patients with diabetes mellitus and periapical lesion have shown notably diminished healing succeeding endodontic therapy. 6 Hence, this study aims to isolate obligate anaerobes and facultative anaerobes from root canal of non-vital teeth in diabetic (Type II) and non-diabetic patients.…”
Section: Ijcrr Section: Healthcarementioning
confidence: 99%
“…Comparatively, anaerobic bacteria of the genus Peptostreptococcus, Bacteroides, Propionibacterium and Fusobacterium are often associated (19)(20)(21)(22)(23). These species belong to the same category of anaerobes commonly found in clinical specimens (24,26,27). Many of these species produce beta-lactamase and harbour antibiotic resistant genes that may contribute to drug failure (28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic organisms are aetiologic agents of serious infections in human and have been documented to be the major causative agents of otitis media, oro-dental infections, puerperal sepsis, lung abscesses and intra-abdominal sepsis 1 2 . Culture and isolation of these organisms are not easy due to their fastidious nature.…”
mentioning
confidence: 99%